Optimization The Rule Of “Mubalighot Motivator Kesehatan Aisyiyah” In Breastfeeding Self Efficacy - Ihda Mauliyah; Ratih Indah Kartikasari (poltekkes kemenkes mataram, 2020)
Breastfeeding Self Efficacy (BSE) is a mother's belief regarding her ability to breastfeed her baby and decide whether the mother chooses to breastfeed or not. Aisyiyah through the Health Council has a program to increase the level of public health, especially women, infants, and children based on health services and community based on the spirit of al-Ma'un by increasing efforts to reduce maternal mortality through various activities and increasing efforts to reduce the numbers of infant and toddler deaths with one of priority which is exclusive breastfeeding through qoryah Thoyyibah program held by Balai Sakinah Aisyiyah. The design this study used Pre Experimental design with One Group Pretest-Posttest approach. Samples were pregnant women trimester III until the period of the puerperium (6 weeks) in the sub-district now Lamongan pregency of 20 postpartum mothers. Initial assessment was conducted to assess Early Breasfeeding Self Efficacy in pregnant women. The intervention was carried out by providing health care education by holding Mubalighot health motivators so that they were able to educate postpartum mothers. Furthermore, an Early Breasfeeding Self Efficacy assessment was reconducted. Data were analyzed by Wilcoxon Sign Rank test using SPSS.25. The results showed that the significance level (p) = 0.046 <α = 0.05 Ho was rejected which means that there was a significant influence between Breasfeeding Self Efficacy before and after conducting Mubalighot health motivator. This shows that the role of Mubalighot health motivator for Aisyiyah